The evaluation of new multi-material human soft tissue simulants for sports impact surrogates. (January 2015) - Payne, Thomas; Mitchell, Séan; Bibb, Richard; Waters, Mark
Abstract: Previous sports impact reconstructions have highlighted the inadequacies in current measures to evaluate the effectiveness of personal protective equipment (PPE) and emphasised the need for improved impact surrogates that provide a more biofidelic representation of human impact response. The skin, muscle and subcutaneous adipose tissues were considered to constitute the structures primarily governing the mechanical behaviour of the human body segment. A preceding study by Payne et al. (in press) investigated the formulation and characterisation of muscle tissue simulants. The present study investigates the development of bespoke blends of additive cure polydimethysiloxane (PDMS) silicones to represent both skin and adipose tissues using the same processes previously reported. These simulants were characterised mechanically through a range of strain rates and a range of hyperelastic and viscoelastic constitutive models were evaluated to describe their behaviour. To explore the worth of the silicone simulants, finite element (FE) models were developed using anthropometric parameters representative of the human thigh segment, derived from the Visible Human Project. The multi-material silicone construction was validated experimentally and compared with both organic tissue data from literature and commonly used single material simulants: Dow Corning Silastic 3480 series silicones and ballistics gelatin when subject to a representative sports specific knee impact. Superior biofidelic performance is reported for the PDMS silicone formulations and surrogate predictions. Highlights: Bespoke PDMS silicones were formulated for skin and adipose. Materials characterised to determine behaviour at a range of strain rates. FE models generated using hyperelastic and viscoelastic constitutive models. FE models validated for PDMS surrogates and previous single material stimulants. PDMS model show more biofidelic impact response compared to other stimulants.